Pheophytin Derived Near‐Infrared‐Light Responsive Carbon Dot Assembly as a New Phototheranotic Agent for Bioimaging and Photodynamic Therapy. Issue 12 (28th May 2019) - Wen, Yongmei; Jia, Qingyan; Nan, Fuchun; Zheng, Xiuli; Liu, Weimin; Wu, Jiasheng; Ren, Haohui; Ge, Jiechao; Wang, Pengfei
Abstract: Carbon dots (CDs), a kind of phototheranostic agent with the capability of simultaneous bioimaging and phototherapy [i.e., photodynamic therapy (PDT) or photothermal therapy (PTT)], have received considerable attention because of their remarkable properties, including flexibility for surface modification, high biocompatibility, low toxicity and photo‐induced activity for malignant tumor cells. Among numerous carbon sources, it has been found that natural biomass are good candidates for the preparation of CD phototheranostic agents. In this study, pheophytin, a type of Mg‐free chlorophyll derivative and also a natural product with low toxicity, was used as a raw carbon source for the synthesis of CDs by using a microwave method. The obtained hydrophobic CDs exhibited a maximum near‐infrared (NIR) emission peak at approximately 680 nm, and high singlet oxygen ( 1 O2 ) generation with a quantum yield of 0.62. The self‐assembled CDs from the as‐prepared CDs with DSPE‐mPEG2000 retained efficient 1 O2 generation. The obtained carbon dot assembly was not only an efficient fluorescence (FL) imaging agent but also a smart PDT agent. Our studies indicated that the obtained hydrophilic CD assembly holds great potential as a new phototheranostic agent for cancer therapy. This work provides a new route for synthesis of CDs and proposes a readily available candidate for tumor treatment. Abstract : Joining the dots : A carbot dot assembly derived from pheophytins for fluorescence imaging and synergistic photodynamic therapy of cancer is reported.